Problems of protection of labor rights during hiring with the use of artificial intelligence algorithms - Vavzhenchuk, Sergiy; Zhmaka, Vladyslav (Problems of legality, 2024)
Abstract In recent years, artificial intelligence has found wide application in labor law, including in hiring processes. Artificial intelligence algorithms are used to automate recruiting, skills assessment and decision making. Although this can provide certain advantages and efficiency in the selection of candidates, the use of artificial intelligence algorithms in hiring also creates new legal problems and challenges, in particular in the context of the protection of labor rights in hiring: discrimination, transparency of artificial intelligence algorithms, protection of personal data. The problems caused by the use of artificial intelligence in labor law create challenges for lawyers in the context of creating ethical criteria and legal frameworks that regulate the use of artificial intelligence in the hiring process. The purpose of this article is to outline the main legal issues related to the violation and protection of labor rights in the case of the use of artificial intelligence algorithms in hiring. To achieve the goal of the research, methods of analysis, generalization, formal-logical, comparison, forecasting, dialectical and others were used. The current state of Ukrainian legislation and the experience of foreign countries are considered. The signs by which the artificial intelligence system can be classified as high-risk are highlighted. The problems of personal data protection during recruitment using artificial intelligence algorithms are analyzed. The definition of discrimination contained in international legal acts has been studied. Insufficient legal regulation of discrimination with the use of artificial intelligence algorithms has been established, which in turn creates problems in law enforcement. The criteria necessary to prevent manifestations of discrimination during recruitment with the use of artificial intelligence algorithms are highlighted. On the basis of the conducted research, a conclusion was made about the insufficient legal regulation of the use of artificial intelligence algorithms in domestic legislation, criteria that should become key for the protection of labor rights during employment with the use of artificial intelligence algorithms.